1999
DOI: 10.1046/j.1523-1739.1999.97443.x
|View full text |Cite
|
Sign up to set email alerts
|

The Appropriateness of Puppet‐Rearing Birds for Reintroduction

Abstract: Captive propagation and reintroduction programs for rare and endangered species rarely include testing of techniques prior to initiation of recovery efforts. To experimentally test the effects of rearing social, altricial birds with or without a conspecific, parental model (a puppet), we used Common Ravens (Corvus corax) in southwestern Idaho as surrogates for the endangered Hawaiian Crow (Corvus hawaiiensis) and Mariana Crow (Corvus kubaryi). A puppet is believed to reduce sexual and filial imprinting on huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…For species that have a tendency to habituate, it is also crucial to reduce any human contact during their upbringing in captivity (e.g. through puppet-rearing of chicks, Valutis & Marzluff, 1999).…”
Section: Animal Behavior Difficultiesmentioning
confidence: 99%
“…For species that have a tendency to habituate, it is also crucial to reduce any human contact during their upbringing in captivity (e.g. through puppet-rearing of chicks, Valutis & Marzluff, 1999).…”
Section: Animal Behavior Difficultiesmentioning
confidence: 99%
“…For example, hand rearing of captive animals has been criticized for the likelihood that abnormal behaviors will occur after release; however, the perception that parent‐rearing methods will always be superior is being challenged by the results of a number of well‐designed experimental studies (Kreger et al 2005). For example, hand rearing with puppets results in increased vigilance and possibly contributes to increased survival of the Common Raven ( Corvus corax ), used as a model for the Hawaiian Crow ( C. hawaiiensis ) and the Mariana Crow ( C. kubaryi ) (Valutis & Marzluff 1999). Results of a 4‐year experiment comparing hand‐reared and parent‐reared Mississippi Sandhill Cranes ( Grus canadensis pulla ) demonstrated that hand‐reared cranes had better postrelease survival (Ellis et al 2000).…”
Section: Experiments To Mitigate the Effects Of Captivity In Reintrodmentioning
confidence: 99%
“…Limited contact with humans prevents tameness. For instance, use of puppet-rearing parents can be envisaged for birds (Valutis & Marzluff 1999). (b) To limit later genetic introgression in the wild target population the strain used in captivity should be as genetically close as possible to the former.…”
Section: Implications For Management and Policy-makingmentioning
confidence: 99%